Drug Transporter Protein Quantification of Immortalized Human Lung Cell Lines Derived from Tracheobronchial Epithelial Cells (Calu‐3 and BEAS2‐B), Bronchiolar–Alveolar Cells (NCI‐H292 and NCI‐H441), and Alveolar Type II‐like Cells (A549) by Liquid Chromatography–Tandem Mass Spectrometry. Issue 9 (17th February 2015) - Sakamoto, Atsushi; Matsumaru, Takehisa; Yamamura, Norio; Suzuki, Shinobu; Uchida, Yasuo; Tachikawa, Masanori; Terasaki, Tetsuya; Donovan, Maureen D.; Langguth, Peter; Polli, James E.; Tamai, Ikumi; Vig, Balvinder; et al.
<x xml:space="preserve">Abstract</x> Understanding the mechanisms of drug transport in the human lung is an important issue in pulmonary drug discovery and development. For this purpose, there is an increasing interest in immortalized lung cell lines as alternatives to primary cultured lung cells. We recently reported the protein expression in human lung tissues and pulmonary epithelial cells in primary culture, (Sakamoto A, Matsumaru T, Yamamura N, Uchida Y, Tachikawa M, Ohtsuki S, Terasaki T. 2013. J Pharm Sci 102(9):3395–3406) whereas comprehensive quantification of protein expressions in immortalized lung cell lines is sparse. Therefore, the aim of the present study was to clarify the drug transporter protein expression of five commercially available immortalized lung cell lines derived from tracheobronchial cells (Calu‐3 and BEAS2‐B), bronchiolar–alveolar cells (NCI‐H292 and NCI‐H441), and alveolar type II cells (A549), by liquid chromatography–tandem mass spectrometry‐based approaches. Among transporters detected, breast cancer‐resistance protein in Calu‐3, NCI‐H292, NCI‐H441, and A549 and OCTN2 in BEAS2‐B showed the highest protein expression. Compared with data from our previous study, (Sakamoto A, Matsumaru T, Yamamura N, Uchida Y, Tachikawa M, Ohtsuki S, Terasaki T. 2013. J Pharm Sci 102(9):3395–3406) NCI‐H441 was the most similar with primary lung cells from all regions in terms of protein expression of organic cation/carnitine transporter 1 (OCTN1). In conclusion, the protein expression profiles of transporters in five immortalized lung cell lines were determined, and these findings may contribute to a better understanding of drug transport in immortalized lung cell lines. © 2015 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:3029–3038, 2015